Ethics and the Daily Language of Medical Discourse - Poirier, Suzanne (The Hastings Center report, 1988)
The standard medical case report often reduces patients and caregivers to complexes of medical facts and clinical decisions. Restructuring the genre itself to acknowledge the human dimensions of both patients and physicians allows questions of human values to regain their stature as integral components of the discourse.